Vestibular rehabilitation using video gaming in adults with dizziness: a pilot study. Issue 3 (7th March 2018) - Phillips, J S; Fitzgerald, J; Phillis, D; Underwood, A; Nunney, I; Bath, A
Abstract: Objective: To determine the effectiveness of vestibular rehabilitation using the Wii Fit balance platform, in adults with dizziness. Methods: A single-site prospective clinical trial was conducted in a university hospital in the UK. Forty patients with dizziness, who would normally be candidates for vestibular rehabilitation, were identified and considered as potential participants. Participants were randomised into either the treatment group (the Wii Fit group) or the control group (standard customised vestibular rehabilitation protocol). Participants were assessed over a 16-week period using several balance and quality of life questionnaires. Results: Both exercise regimes resulted in a reduction of dizziness and an improvement in quality of life scores over time, but no statistically significant difference between the two interventions was identified. Conclusion: This pilot study demonstrated that use of the Wii Fit balance platform resulted in a statistically significant improvement in balance function and quality of life. Furthermore, outcomes were comparable to a similar group of individuals following a standard customised vestibular rehabilitation protocol. The study provides useful information to inform the design and execution of a larger clinical trial.